Anti-Stokes photoluminescence probing k-conservation and thermalization of minority carriers in degenerately doped semiconductors - K. Mergenthaler (Nature Portfolio, 2017)
Anti-Stokes luminescence - the emission of photons with higher energy than those absorbed – in nanomaterials is widely used for optoelectronic applications. Here the authors observe it in degenerately doped bulk InP and GaAs, indicating it as a more general property of direct bandgap semiconductors.